Emotion As a Mediator in The Relationship Between Green Marketing Mix and Green Purchase Intention - Balaji, K.; Benny, Ashley Dominic; Gunawan, Theresia (Indonesian Journal of Sustainability Accounting and Management, 2025)
This study focuses on the key elements of green marketing mix and its impact on green purchase intention through positive and negative anticipative emotion. This study has contributed an array of results that prove to be insightful for the marketers of electrical two-wheeler vehicles in India. Data was collected from 367 respondents and PLS-SEM is used for the analysis. The direct effects of green product, green place and green promotion on green purchase intention are not significant and these factors do not have a direct impact on purchase intention. Green price alone has direct impact on Purchase intention. Upon testing the indirect path effect, it is confirmed that positive anticipative emotion plays mediating role between Green Product, Place, Promotion, and purchase intention. Further negative anticipative emotion acts as a mediator between Green Product, Price, Place, Promotion and Purchase Intention. The marketers to provoke purchase intention among the customers they use green marketing mix as their main constructs. But delving further into green marketing mix and its impact on purchase intention it is clearly identified that both positive and negative anticipated emotion move unipolarly carry out an intention to purchase electric two wheelers within the minds of the customers.